What the Milky Way bulge reveals about the initial metallicity gradients in the disc. Issue Volume 14:Issue A30(2018) (August 2018) - Fragkoudi, F.; Di Matteo, P.; Haywood, M.; Khoperskov, S.; Gomez, A.; Schultheis, M.; Combes, F.; Semelin, B.
Abstract: We examine the metallicity trends in the Milky Way (MW) bulge – using APOGEE DR13 data – and explore their origin by comparing two N-body models of isolated galaxies which develop a bar and a boxy/peanut (b/p) bulge. Both models have been proposed as scenarios for reconciling a disc origin of the MW bulge with a negative vertical metallicity gradient. The first is a superposition of co-spatial disc populations, different scaleheights and metallicities (with flat gradients) where the thick, metal-poor populations contribute significantly to the stellar mass budget in the inner galaxy. The second model is a single disc with an initial steep radial metallicity gradient which gets mapped by the bar into the b/p bulge in such a way that the vertical metallicity gradient of the MW bulge is reproduced – as shown already in previous works in the literature. As we show here, the latter model does not reproduce the positive longitudinal metallicity gradient of the inner disc, nor the metal-poor innermost regions seen in the data. The model with co-spatial thin and thick disc populations reproduces all the aforementioned trends. We therefore see that it is possible to reconcile a (primarily) disc origin for the MW bulge with the observed trends in metallicity by mapping the inner thin and thick discs of the MW into a b/p.